Optimizing the rate capability of nickel cobalt phosphide nanowires on graphene oxide by the outer/inter-component synergistic effects. Issue 4 (18th December 2019) - Jing, Chuan; Song, Xianyu; Li, Kailin; Zhang, Yumeng; Liu, Xiaoying; Dong, Biqin; Dong, Fan; Zhao, Shuangliang; Yao, Hongchang; Zhang, Yuxin
Abstract : Bimetallic phosphides have been identified as promising alternative electrode materials owing to their admirable conductivity and electrochemical activity. Abstract : Bimetallic phosphides have been identified as promising alternative electrode materials owing to their admirable conductivity and electrochemical activity. Nevertheless, the severe agglomeration of single-component bimetallic phosphides hinders their extensive applications. Moreover, current research lacks in-depth studies on the effect of outer/inter-component synergy on the rate capability. In this study, novel nickel cobalt phosphide nanowires on two-dimensional graphene oxide nanosheets (GO@NiCoP) were designed and prepared by combining a hydrothermal process and phosphorization. GO served as the conductive path to improve the composite conductivity and provided abundant oxygen-containing functional groups to coordinate with the metal cations of NiCoP, thereby boosting the overall structural stability. NiCoP possesses an optimal intercomponent synergistic effect, such as an optimal –OH − adsorption energy and deprotonation energy, leading to an enhanced potential of the electrochemical reaction. Taking advantage of these materials, the GO@NiCoP electrode displayed a high specific capacitance of 1125 F g −1 (155 mA h g −1 ) at 2 A g −1 and a high cycling stability of 104.88% capacitance retention after 5000 cycles at 30 A g −1 . Interestingly, the GO@NiCoP electrode delivered an exceptional rate capability of 84.09% capacitance retention at 20 A g −1 and 39.77% capacitance retention at 60 A g −1 owing to its stable structure and excellent conductivity. In addition, we fabricated a GO@NiCoP//AG ASC device that delivered a desirable energy density of 27.71 W h kg −1 at 788 W kg −1 . To broaden its applications, a self-charging power system with a satisfactory lighting time was constructed using the ASC device. In short, the outstanding electrochemical performance of the electrode materials provides a novel perspective for enhancing the rate capacity of electrode materials by the outer/inter-component synergistic effect.